Foundations for a disequilibrium theory of the business cycle : qualitative analysis and quantitative assessment - Chiarella, Carl.; Flaschel, Peter, 1943-; Franke, Reiner (Cambridge, UK ; New York : Cambridge University Press, 2005)
"Building on The Dynamics of Keynesian Monetary Growth by Chiarella and Flaschel (2000), this book is a key contribution to business cycle theory, setting out a disequilibrium approach with gradual adjustments of the key macroeconomic variables. Its analytic study of a deterministic model of economic activity, inflation and income distribution integrates elements in the tradition of Keynes, Metzler and Goodwin. After a qualitative analysis of the basic feedback mechanisms, the authors calibrate the KMG model to the stylized facts of the business cycle in the US economy, and then undertake a detailed numerical investigation of the local and global dynamics generated by the model.
Finally, topical issues in monetary policy are studied in small macromodels as well as for the KMG model by incorporating an estimated Taylor-type interest rate reaction function. The stability features of this enhanced model are also compared to those of the original KMG model."--Jacket
Foreword / J. Barkley Rosser, Jr. -- 1. Competing approaches to Keynesian macrodynamics -- 2. AS-AD growth theory : a complete analysis of the textbook model -- 3. Disequilibrium growth : the point of departure -- 4. The Keynes-Metzler-Goodwin model -- 5. Calibration of three wage-price modules -- 6. Calibration of the full KMG model -- 7. Subsystems and sensitivity analysis of the KMG model -- 8. The Taylor rule in small macromodels -- 9. Incorporating the Taylor rule into KMG.
Includes bibliographical references (pages 505-513) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Business cycles -- Econometric models; Equilibrium (Economics); Cycles économiques -- Modèles économétriques.; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Macroeconomics; Business cycles -- Econometric models; Equilibrium (Economics); Electronic books; Electronic books